2020
DOI: 10.5530/pj.2020.12.103
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification Similarity and Qualitative Expression of Metallothionein Gene in IR-Bagendit Rice (Oryza sativa)

Abstract: Metallothionein (MTs) is an enzyme that plays a role in the binding of metals in plants. Various types of rice have been known to contain MTs and IR-Bagendit rice leaves have the highest MTs protein content compared to other rice varieties. However, MTs coding gene in IR-Bagendit rice variety is still unknown. OsRAC1 gene is reported as the down-regulator of MTs and there is an analogous gene for MTs-like gene using RAP1 and RAP2 primers in various plants. This study aimed to isolate, identification of similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Such conditions could damage kidney cells. 15,5 The decrease in the body's antioxidants and the increase in free radicals will cause oxidation and escalate lipid peroxidation. Unstable lipid peroxidation can damage three types of compounds that significantly maintain cell integrity; they are cell membranes, proteins, and DNA.…”
Section: Necrosis Normal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conditions could damage kidney cells. 15,5 The decrease in the body's antioxidants and the increase in free radicals will cause oxidation and escalate lipid peroxidation. Unstable lipid peroxidation can damage three types of compounds that significantly maintain cell integrity; they are cell membranes, proteins, and DNA.…”
Section: Necrosis Normal Cellsmentioning
confidence: 99%
“…Therefore, metallothionein can be used as a biomarker of heavy metal exposure. 15 This study aims to determine the functions of IR-Bagendit rice leaf infusion from Blora to prevent degeneration and necrosis of renal tubular cells.…”
Section: Introductionmentioning
confidence: 99%
“…IR Bagendit rice leaves-infused water is rich in the metallothionein protein (Santosa et al, 2018;Santosa et al, 2020) and has many sulfhydryl groups that function in the HG detoxication mechanism. A large number of sulfhydryl groups in the metallothionein protein affects the protein's ability to bind Hg.…”
Section: Introductionmentioning
confidence: 99%
“…The binding coordination of each metal ion of the Cys forms a tetrahedral structure of tetrathionate (Nezhad RM, Shahpiri A, 2013). A previous study has proven that metallothionein genes in chromosome 3 function as a protein induced by environmental stresses, such as the presence of metallic contaminants (Santosa et al, 2020) Coconut water drink is found in tropical countries, such as Indonesia. Moreover, coconut water has been commonly consumed as a thirst-quenching drink.…”
Section: Introductionmentioning
confidence: 99%